Effect of deep breathing training on exercise induced changes of respiratory parameters in normal young volunteers - Hun, Wee Siok (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
Life begins with our first breath and ends with our last breath. Through the process of breathing man is connected to the world around him. One can live for a long time without food, few days without water, but without breathing, man, s life is measured in minutes (Kanty Koontz, 2000). Something so essential definitely deserves our attention. Breathing is the most important of all the bodily functions; in fact all the other bodily functions depend on breathing. According to Rev. James Vinson Wingo (2000) humans are dependent on breathing for life and correct breathing habits are important for continued vitality of the body and freedom from diseases. Breathing is important for two reasons. First, it is the only means by which our body receives the supply of oxygen which is vital for our survivaL Second, breathing is one of the routes through which waste products and toxins are removed ftom the body (Rosemary A. Payne, 2000). Breathing is an act in which we take air from atmosphere into our lungs, absorb the oxygen from it into our blood, and expel the air again into the atmosphere together with carbon dioxide and water vapour. During normal relaxed breathin& abdomen gently moves forward and backward as the air moves in and out This is due to the fact that the diaphragm presses down on contents of the stomach during inspiration causing it to bulge out (Jacob Mathew, 1998). This act of inhalation and exhalation is repeated every 4 to 5 seconds. This normally we breathe about 15 times every minute and 20,000 times per day, each time taking about 500 ml of air per breath (Benjamin Levine MD, 1998; Nancy Zi, 1998). However, the respiratory rate is not constant and the breathing pattern changes markedly under various physiological and pathological conditions. Simple physiological activities like walking, lifting some articles, carrying loads, climbing the stairs, running, doing any simple physical exercise or emotional disturbances increase the mte and depth of respiration. Some pathological changes that affect lungs like tuberculosis and bronchitis also change the pattern of breathing (Benjamin Levine MD, 1998). A new born baby breathes with the abdomen. As the child gets older, breathing becomes partially intercostal (chest breathing). During adult life, most of the people breathe only through the chest Abdominal breathing (maximal use of the diaphragm) is almost forgotten (Jacob Mathew, 1998), so much so that when the person tries to inhale, his chest expands but the abdomen moves in, which is abnormal. It makes the breathing process less effective because it not only promotes shoulder muscle tension, but also prevents the air from getting to the base of the lungs (Randall Helm. P. T, 1997).